High awareness, low compliance: rabies knowledge and dog ownership practices among pastoralists, Marsabit County, Kenya - Gitonga, Pauline N.; Ogoti, Brian; Etapar, Teresa Lopuwa; Coetzer, Andre (Frontiers in Veterinary Science, 2025)
IntroductionRabies is a fatal yet preventable zoonotic disease that disproportionately affects underserved communities in endemic regions. Understanding community-level Knowledge, Attitudes, and Practices (KAP) is essential for designing effective rabies control programs, particularly in remote pastoralist settings where access to healthcare and information is limited. This study assessed community knowledge, attitudes, and practices regarding rabies and dog ownership among pastoralist communities in Marsabit County, Kenya. It aimed at evaluating levels of rabies knowledge and dog care practices across demographic groups to identify gaps that could inform locally appropriate prevention strategies.MethodsA cross-sectional KAP survey was conducted in May 2023 among 411 households using a structured questionnaire, with stratified random sampling employed to ensure village-level representation.ResultsOverall, 86.1% of respondents demonstrated adequate knowledge of rabies, with slightly higher knowledge among dog owners (87.0%). However, only 18.8% of dog owners met the threshold for responsible ownership. Among dog owners, rabies vaccination coverage was just 22%, highlighting a significant knowledge-practice gap. Willingness to pay for dog sterilisation surgery was a significant predictor of rabies knowledge (aOR 2.95, 95% CI: 1.33–7.22, p = 0.0110), while gender was the only significant predictor of responsible dog ownership, with females having lower odds (aOR 0.50, 95% CI: 0.25–1.02, p = 0.0495).DiscussionDespite high levels of rabies knowledge, preventive practices such as vaccination, deworming, and responsible dog ownership remain suboptimal in Loiyangalani town. A multifaceted, community-based approach is urgently needed to close the knowledge–practice gap and advance rabies elimination goals in remote pastoralist communities.